Market Perspective Determinants for Stock Returns in Manufacturing Companies on the IDX - Widianingtyas, Rifa Pramesti; Irawati, Zulfa (Prosiding University Research Colloquium, 2023)
he purpose of this study was to analyze the effect of Economic Value Added (EVA), Price to Book Value (PBV), Earning Per Share (EPS) on stock returns. This study uses a quantitative descriptive method. The data sources used are secondary data sources, in the form of financial report data from food and beverage manufacturing sector companies listed on the Indonesia Stock Exchange from 2019-2021 and annual reports. The object of this research is a food and beverage manufacturing company that is listed on the IDX in 2019-2021. The analytical method used is descriptive statistical analysis, classic assumption test, namely: normality test, multicollinearity test, autocorrelation test and heteroscedasticity test and multiple linear regression analysis. Then do the t test and F test. Data collection techniques using purposive sampling method. The results in this study partially, Economic Value Added (EVA) and Earning Per Share (EPS) have a positive and significant effect on stock returns. While simultaneously Economic Value Added (EVA), Price to Book Value (PBV) and Earning Per Share (EPS) together influence stock returns.